The Bible's Writings: An Introduction for Christians and Jews - Zucker, David J (Wipf and Stock Publishers, 2013)
Intro -- Title Page -- Foreword -- Chapter 1: Introduction to the Writings/Ketuvim -- Chapter 2: Psalms -- Chapter 3: Proverbs -- Chapter 4: Job -- Chapter 5: Song of Songs -- Chapter 6: Ruth -- Chapter 7: Lamentations -- Chapter 8: Ecclesiastes -- Chapter 9: Esther -- Chapter 10: Daniel -- Chapter 11: Ezra -- Chapter 12: Nehemiah -- Chapter 13: Chronicles (1 and 2) -- Glossary -- Bibliography.